2005
DOI: 10.1002/ajmg.a.30515
|View full text |Cite
|
Sign up to set email alerts
|

GJB2 mutations in keratitis‐ichthyosis‐deafness syndrome including its fatal form

Abstract: Keratitis-ichthyosis-deafness syndrome (KID; MIM 148210) is a rare congenital disorder characterized by vascularizing keratitis, sensorineural hearing loss (HL), and progressive erythrokeratoderma. Clinical variability including a fatal course of KID in the first year of life has been reported. Germline missense mutations in GJB2, encoding connexin-26, were recently found to cause KID in 14 unrelated juvenile and adult patients. We identified a de novo GJB2 mutation G45E in a patient displaying the fatal form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
85
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 24 publications
10
85
1
Order By: Relevance
“…While the rare fatal form of KIDS has been associated with Cx26-G45E in two unrelated Caucasian patients (14,17,21), it has also been linked to recessive nonsyndromic deafness in some Asian populations. In a large study of Japanese patients with nonsyndromic SNHL, G45E was detected in 16% of the GJB2 disease alleles (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the rare fatal form of KIDS has been associated with Cx26-G45E in two unrelated Caucasian patients (14,17,21), it has also been linked to recessive nonsyndromic deafness in some Asian populations. In a large study of Japanese patients with nonsyndromic SNHL, G45E was detected in 16% of the GJB2 disease alleles (26).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report the functional characteristics of a Cx26 mutation (G45E) that was observed in two previously described infants with a rare fatal form of KIDS. The children harboring the G45E mutation in GJB2 had congenital deafness, hyper-keratosis of the skin, and recurrent severe skin infections, which eventually lead to septicemia and death within the first year of life (14,17,21). Using an in vitro expression assay, we show that Cx26-G45E hemichannels display a significant increase in membrane current flow that results in cell death.…”
mentioning
confidence: 99%
“…In that study, we showed that gap junctions containing p.Gly45Glu-mutant-Cx26 displayed aberrant gating activity (7). Indeed, the same heterozygous de novo p.Gly45Glu mutation in GJB2 has been previously reported to underlie a severe form of KID syndrome in an Austrian patient (8). Both these cases died from KID syndrome.…”
Section: Discussionmentioning
confidence: 79%
“…However, the present case is not consistent with KID syndrome for a number of reasons: (1) it did not show any dermal diseases; (2) pituitary dwarfi sm is not a complication of KID disease; and (3) KID syndrome is caused by the GJB2 gene, which encodes Connexin 26 and maps to 13q11-12. 1 Although the etiology of this case is unknown, we speculate that a chromosomal translocation t(3;9)(p27;p13) may have induced partial ectodermal dysplasia, including LSCD.…”
Section: Commentsmentioning
confidence: 95%
“…[1][2][3] Most IOFBs require surgical extraction because if the IOFB remains in the globe it may cause secondary damage to both the eyeball and vision. 4,5 However, some inert IOFBs such as fragments of glass, china, gold, and sand may be left alone if they are stationary and out of the visual axis.…”
Section: Glass Fragment In the Anterior Chamber Caused Corneal Endothmentioning
confidence: 99%